Effects of Nutrients in Substrates of Different Grains on Aflatoxin B(1) Production by Aspergillus flavus - Liu, Jie (Hindawi Publishing Corporation, 2016)

(untitled) (Biomed Res Int)
The current study was to better understand the potential factors affecting aflatoxin B(1) (AFB(1)) accumulation varies between different grains. The nutrient composition and contents of defatted substrates were determined; additionally, according to the nutrient content of the substrates, the effects of starch, soluble sugars, amino acids, and trace elements on AFB(1) production and mycelial growth in Czapek-Dox medium were examined. These results verified that removal of lipids from ground substrates significantly reduced the substrate's potential for AFB(1) production by Aspergillus flavus. Maltose, glucose, sucrose, arginine, glutamic acid, aspartic acid, and zinc significantly induced AFB(1) production up to 1.7- to 26.6-fold. And stachyose more significantly promoted A. flavus growth than the other nutrients. Thus, this study demonstrated that, combined with the nutrients content of grains, in addition to lipids, sucrose, stachyose, glutamic acid, and zinc might play key roles in various grains that are differentially infected by A. flavus. Particularly, two new nutrients (arginine and stachyose) of the grains we found significantly stimulate AFB(1) production and A. flavus growth, respectively. The results provide new concepts for antifungal methods to protect food and animal feed from AFB(1) contamination.